The endocast of the late Middle Paleolithic Manot 1 specimen, Western Galilee, Israel. Issue 160 (November 2021) - Grimaud-Hervé, Dominique; Albessard-Ball, Lou; Pokhojaev, Ariel; Balzeau, Antoine; Sarig, Rachel; Latimer, Bruce; McDermott, Yvonne; May, Hila; Hershkovitz, Israel
Abstract: Studying endocasts has long allowed anthropologists to examine changes in the external topography and the overall size of the brain throughout the evolutionary history of hominins. The nearly complete calvaria of Manot 1 presents an opportunity to gain insights into the external brain morphology, vascular system, and dimensions of the brain of this late Middle Paleolithic hominin. Detailed size and shape analyses of the Manot 1 endocast indicate a modern Homo sapiens anatomy, despite the presence of some primitive features of the calvaria. Traits considered to be derived endocranial features for H. sapiens are present in Manot 1, including an elongated parietal sagittal chord with an elevated superior part of the hemisphere, a widened posterior part of the frontal lobes, a considerable development of the parietal reliefs such as the supramarginal lobules, and a slight posterior projection of the occipital lobes. These findings, together with data presented in previous studies, rule out the possibility of a direct Neanderthal ancestry for the Manot 1 hominin and instead confirm its affiliation with H. sapiens . The Manot 1 calvaria is more similar to that of later Upper Paleolithic H. sapiens than it is to the earlier Levantine populations of Skhul and Qafzeh. The late Middle Paleolithic date of Manot 1 provides an opportunity to analyze the recent developments in human cerebral morphology and organization.